Demographic transition in two regions of southern Brazil: cases of Corede Celeiro and AMEOSC (Research, Society and Development, 2021)
This article investigates the demographic behavior of two regions in southern Brazil: that of the Regional Development Council (Corede Celeiro), in Rio Grande do Sul, and the Association of Municipalities in the Far West of Santa Catarina (AMEOSC), in the years 2000 and 2010. The study is divided into three themes: fecundity, aging and the migratory pattern. The intention is to verify how the demographic transition process is taking place by establishing a comparison between the regions and identifying possibilities for actions to minimize the effects of this new dynamic. The research, which has a qualitative methodology, is of a descriptive-exploratory nature. Considering that in the year 2020, there was no Demographic Census due to the new Coronavirus, for the study, data from the last two IBGE Censuses were used, in addition to previous research on such regions. As a result, it was observed that the Corede Celeiro region had a significant population loss, mainly in the number of children and Economically Active Population (PEA); the elderly segment increased, signaling an advanced demographic transition process. In the AMEOSC region, there was an increase in the number of inhabitants, a reduction in fecundity and an increase in the number of elderly people, also demonstrating a process of demographic transition, although even more intense than Celeira region. It was also found that a significant exchange of population between the two regions, a fact that highlights the relevance that geographical proximity has for the regional development.